1979
DOI: 10.1111/j.1432-1033.1979.tb06287.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Membrane-Bound Inorganic Pyrophosphatase in Rhodospirillum rubrum

Abstract: The membrane‐bound inorganic pyrophosphatase (EC 3.6.1.1) from Rhodospirillum rubrum has been investigated with the tools of enzyme kinetics, and with two amino acid reagents, N‐ethyl‐maleimide (MalNET) and 4‐chloro‐7‐nitrobenzofurazan (Nbf‐Cl). The concentration of the true substrate, MgPPi, was varied with constant concentrations of free Mg2+ or PPi. It was observed that Mg2+ acted as an activator. Heat inactivation of the enzyme at 62°C was slowed down in the presence of Mg2+. MalNET and Nbf‐Cl bind to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…25-kDa subunit), with a K m for MgPP i of 20 to 30 M (29), and an H ϩ -PPase (ca. 60 kDa subunit), an integral membrane protein whose K m for MgPP i is in the range of 0.1 to 0.2 mM (47). In contrast to the situation in photosynthetic eukaryotic tissues that lack a cytosolic sPPase (57), PP i generated in bacterial cell anabolism is presumably accessible to both PPases, since a coordinated regulation is needed in order to maintain an adequate \'0fintracellular level of this metabolite (0.5 to 1.0 mM) (32) and a suitable proton gradient across membranes.…”
Section: Discussionmentioning
confidence: 99%
“…25-kDa subunit), with a K m for MgPP i of 20 to 30 M (29), and an H ϩ -PPase (ca. 60 kDa subunit), an integral membrane protein whose K m for MgPP i is in the range of 0.1 to 0.2 mM (47). In contrast to the situation in photosynthetic eukaryotic tissues that lack a cytosolic sPPase (57), PP i generated in bacterial cell anabolism is presumably accessible to both PPases, since a coordinated regulation is needed in order to maintain an adequate \'0fintracellular level of this metabolite (0.5 to 1.0 mM) (32) and a suitable proton gradient across membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these conclusions, we found that the A. tumefaciens H ϩ -PPase, the sequence of which has Lys and Thr in the positions investigated (31), is K ϩ -insensitive. Only another proteobacterial H ϩ -PPase has been biochemically characterized, the enzyme from R. rubrum (38,42,43). As this enzyme, the H ϩ -PPase from A. tumefaciens, was sensitive to inhibition by aminomethylenediphosphonate, dicyclohexylcarbodiimide, and N-ethylmaleimide and has low sensitivity to the soluble pyrophosphatase inhibitor fluoride (Fig.…”
Section: Identification Of Organelles In Bacteria 29975mentioning
confidence: 99%
“…A K ϩ transporting function was proposed for K ϩ -dependent H ϩ -PPases (23), but this issue is still a matter of controversy (14,24). Both K ϩ -dependent and K ϩ -independent H ϩ -PPases are inactivated by sulfhydryl modifying reagents (25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%